2020
DOI: 10.3390/cancers12092562
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Heterotopic Human Colon Xenograft Tumors in Mice with 5-Fluorouracil Attached to Magnetic Nanoparticles in Combination with Magnetic Hyperthermia Is More Efficient than Either Therapy Alone

Abstract: Magnetic nanoparticles (MNPs) have shown promising features to be utilized in combinatorial magnetic hyperthermia and chemotherapy. Here, we assessed if a thermo-chemotherapeutic approach consisting of the intratumoral application of functionalized chitosan-coated MNPs (CS-MNPs) with 5-fluorouracil (5FU) and magnetic hyperthermia prospectively improves the treatment of colorectal cancer. With utilization of a human colorectal cancer (HT29) heterotopic tumor model in mice, we showed that the thermo-chemotherape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 64 publications
(90 reference statements)
0
18
1
Order By: Relevance
“…the induction of thrombogenic collagen fibers. Beyond the previously reported DNA damage and increased stress levels in surviving tumor cells after using themo-combinatorial therapies [8,10,56], we showed that there is also a distinct impact on second messenger and nuclear receptor signaling. The fact that the combined thermo-chemotherapy shared most of the pathways with magnetic hyperthermia illustrates its prominent impact and the synergistically increased effects in presence of very low concentrations of 5FU.…”
Section: Discussioncontrasting
confidence: 41%
“…the induction of thrombogenic collagen fibers. Beyond the previously reported DNA damage and increased stress levels in surviving tumor cells after using themo-combinatorial therapies [8,10,56], we showed that there is also a distinct impact on second messenger and nuclear receptor signaling. The fact that the combined thermo-chemotherapy shared most of the pathways with magnetic hyperthermia illustrates its prominent impact and the synergistically increased effects in presence of very low concentrations of 5FU.…”
Section: Discussioncontrasting
confidence: 41%
“…The reduced interstitial pressure, in turn, enhances permeability of the tumor stroma [ 43 , 44 ] to Dex-MNP. Despite the increased infiltration and consequent low overall heat doses acquired with the use of hyaluronidase, it was hypothesized that tumor growth inhibition would take place and tumor regrowth, which has been repeatedly observed when conducting mild hyperthermia alone [ 34 , 53 ], would also be circumvented. Consistently, tumor depletion was slow but persistent, due to the effects of hyaluronidase I-S.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, over the same time period the cytotoxic effects of thermo-chemotherapy remained stronger than such resulting from MFH monotherapy. Dabaghi et al later demonstrated significant superiority of thermo-chemotherapy compared with 5-Fluouracil monotherapy in vivo in a heterotopic HT 29 xenograft mouse model regarding tumor volume reduction and attenuation of proliferation activity [39]. Interestingly, exclusive MFH treatment also showed significant tumor volume reduction, which was partially attributed to DNA damage in terms of DNA double-strand breaks.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Given this sheer number and the resulting urge for improvement, nanoparticle-based hyperthermia has found its way into the research for novel treatment strategies in colorectal cancer. [38] as well as in vivo [39] in heterotopic xenograft mouse models using the chemotherapeutic doxorubicin and 5-Fluouracil, respectively. Both constituted an additive anti-tumorigenic effect of MFH to the toxicity of the chemotherapeutic agent.…”
Section: Colorectal Cancermentioning
confidence: 99%